Thermodynamics-kinetics of twinning/martensitic transformation in Fe50Mn30Co10Cr10 high-entropy alloy during adiabatic shearing. (May 2020) - Yang, Shuangjun; Yang, Yang
Abstract: Thermodynamics-kinetics of twinning/martensitic transformation during adiabatic shearing in the Fe50 Mn30 Co10 Cr10 high-entropy alloy was firstly quantitatively analyzed. The results indicated that twins and no martensite ε phase were observed within the adiabatic shear band. The critical stress for martensitic transformation was greater than the applied shear stress after 35.2 µs (72.4 µs whole deformation time), and the driving force for ε→γ phase transformation was increasing with increased deformation time, so the original ε phase decreased and finally disappeared. Before 38.3 µs, the critical stress for twinning was lower than the applied shear stress, and twinning occurred. Therefore, twins were observed. Graphical abstract: Image, graphical abstract